Investigation of alloy composition and sintering parameters on the corrosion resistance and microhardness of 316L stainless steel alloy - Ali, S. (Pleiades Publishing, 2019)
Metals used in implant manufacturing include titanium and its alloys, cobalt-chromium and surgical grade stainless steel. Cobalt chromium and titanium alloys can be four to five times more expensive than stainless steel. AISI 316L stainless steel (SS) can be a potential alternative material for implants due to its low cost and adequate mechanical properties. However, the major disadvantage of utilizing SS implants is its contrariness with physiological environment. These SS implants experience a serious assault by interface corrosion when placed in saline solution. This inferior corrosion resistance of SS limits its use as dental implants material. Erosion of dental implants weakens them and implantsâ corrosion causes allergic and hypersensitivity reaction. In order to keep the erosion assault and to upgrade 316L SS similarity with physiological condition, the addition of titanium and boron powders in the 316L SS matrix at the time of manufacture is proposed. This research work examines the effect of boron and titanium addition on the corrosion resistance and micro hardness of 316L SS parts. The amount of boron and titanium addition to the SS matrix is limited to 0.25 and 0.5 wt respectively. The compacts were made at 800 MPa pressure and sintered in the nitrogen atmosphere at 1150 Â°C. The material composition and sintering parameters greatly influenced the properties of the samples. The results of the study revealed that samples with boron and titanium addition had an increase in micro hardness and better corrosion resistance as compared to pure 316L SS sintered samples. Â© Springer Nature Switzerland AG 2019.